Association of race and ethnicity with postpartum contraceptive method choice, receipt, and subsequent pregnancy - David Ngendahimana; Jessica Amalraj; Barbara Wilkinson; Emily Verbus; Mary Montague; Jane Morris; Kavita Shah Arora (BMC, 2021)
Abstract Background We sought to assess racial/ethnic differences in choice of postpartum contraceptive method after accounting for clinical and demographic correlates of contraceptive use. Methods This is a secondary analysis of a single-center retrospective cohort study examining postpartum women from 2012 to 2014. We determined the association between self-identified race/ethnicity and desired postpartum contraception, receipt, time to receipt, postpartum visit attendance, and subsequent pregnancy within 365 days of delivery. Results Of the 8649 deliveries in this study, 46% were by Black women, 36% White women, 12% Hispanic, and 6% by women of other races. Compared with White women, Black and Hispanic women were more likely to have a postpartum contraception plan for all methods. After multivariable analysis, Hispanic women (relative to White women) were less likely to receive their chosen method (odds ratio [OR] 0.74, 95% confidence interval [CI] 0.64-0.87). Women of races other than Black or Hispanic were less likely to experience a delay in receipt of their desired highly-effective method compared to White women (hazard ratio [HR] = 0.70, 95% CI 0.52-0.94). There were no differences between racial/ethnic groups in terms of postpartum visit adherence. Black women were more likely to be diagnosed with a subsequent pregnancy compared to White women (OR 1.17, 95% CI 1.04-1.32). Conclusion Racial/ethnic variation in postpartum contraceptive outcomes persists after accounting for clinical and demographic differences. While intrinsic patient-level differences in contraceptive preferences should be better understood and respected, clinicians should take steps to ensure that the observed differences in postpartum contraceptive plan methods between racial/ethnic groups are not due to biased counseling.